2024
DOI: 10.1108/jrit-09-2023-0129
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the factors affecting the adoption AI techniques in higher education: insights from teachers' perspectives on ChatGPT

Habiba Al-Mughairi,
Preeti Bhaskar

Abstract: PurposeChatGPT, an artificial intelligence (AI)-powered chatbot, has gained substantial attention in the academic world for its potential to transform the education industry. While ChatGPT offers numerous benefits, concerns have also been raised regarding its impact on the quality of education. This study aims to bridge the gap in research by exploring teachers' perspectives on the adoption of ChatGPT, with a focus on identifying factors that motivate and inhibit them to adopt ChatGPT for educational purposes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…ChatGPT dilemma Nguyen (2023) discovered that EFL teachers show enthusiasm for integrating ChatGPT into their writing lessons. Al-Mughairi and Bhaskar (2024) have conducted a qualitative investigation to identify motivating and inhibiting factors in adopting ChatGPT from teachers' perspectives in Oman. In the survey-based research conducted by Kiryakova and Angelova (2023), they found that ChatGPT has a positive attitude toward its application in their teaching activities.…”
Section: Review Of Literaturementioning
confidence: 99%
“…ChatGPT dilemma Nguyen (2023) discovered that EFL teachers show enthusiasm for integrating ChatGPT into their writing lessons. Al-Mughairi and Bhaskar (2024) have conducted a qualitative investigation to identify motivating and inhibiting factors in adopting ChatGPT from teachers' perspectives in Oman. In the survey-based research conducted by Kiryakova and Angelova (2023), they found that ChatGPT has a positive attitude toward its application in their teaching activities.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The reasons why educators choose to use AI tools vary across different fields (Nja et al, 2023). Various factors have been identified as barriers to the adoption of AI tools, including lack of technical support (Nascimento & Meirelles, 2022), ethical concerns (Alanzi et al, 2023), technical complexity (Nguyen et al, 2022), and limited professional development opportunities on AI tools (Al-Mughairi & Bhaskar, 2024). According to Sánchez-Prieto et al (2019), teachers refrain from using AI technologies due to perceived difficulties.…”
Section: Introductionmentioning
confidence: 99%